The Study Physiographic basin of cold water fish farms Shamrood the talent GIs software - Mohamad Reza Aphsharei Azad; Halea Pouraky (نشریه جغرافیا و برنامه‌ریزی, 2015)
Rivers across the nation in terms of conservation, utilization and development of as well as quantitative and qualitative evaluation of favorable river conditions for fish to be used. This study is analysis of factors that is necessary to apply physiographic models of river which have role on topology of stations of fish culture(salmon), in addition to factors which have been used currently in this field, Sham rood river has been studied in terms of physiography. Results of survey among various factors are indicating importance of physiography of studied location that is usable for constructing workshops of fish culture; Sham rood river is regarding to biologic and frequency indices,  its potential power to produce fish is 348 kg.hec. This production is high since Farvardin until Shahrivar and then Khordad has highest amount of fish production. Effective factors include physiographic patterns such as area and perimeter, form of basin, height, inclination, and direction of inclination. These results in analysis of future procedures show condition of topology of fish culture pools' construction and physical and mechanical elements of fish culture such as PH of water, velocity of water flow, light effect, degree of water turbid, suspension solids, solidity of water, electric conduction of water (EC), chemical materials, water salinity, rate of required water show biological factors. Finally, check the condition of steep mountainous watersheds for fish with cold water and put the channel maps, political spots, lithology, slope, aspect factors needed to put them together with the salmon farming appropriate the construction of stations and half fish and unfavorable conditions for fish and plant construction has been determined ..